Walking, Staying In, and Making Sense: Quilting with Pandemic Matter - Peterken, Corinna (Imaginations)

(untitled) (York University, 2021)
This making and making sense are in relation with pandemic matter and a quilt. Matter on hand: fabric, embroidery thread, and appliqué map and speak, sowing sense. The nine blocks sewn and joined together hold their sense making as individual and collective. The conversation from and through making a quilt with pandemic matter emerges from, and plays with, text and image. I align matter and stitching through to hold and turn process into product as I continue making and making sense for knowing about who we are and how to live with each other and the world.